Choosing theme affected PBL - Iwan Zahar (2012)
Choosing a theme in PBL for photography criticism course was a problem, because lecturers had never thought photography criticism, students had a little prior knowledge about photo criticism, social issues and photo history, and also PBL had never been used in in Visual Communication Design, Tarumanagara University. The objective of the research was to design and developed problem-based learning for Tarumanagara student who were learning to interpret photographs. Structured observations, written questionnaires, and oral questionnaires, interviewed were used to gather in depth data of students ‘learning on how to interpret various photo’s themes. The action research conducted in 50 students from visual communication design, fifth semester, Tarumanagara University, Jakarta.